Penetrating gastric ulcer as a manifestation of multisystemic tuberculosis - Espinoza-Ríos, Jorge (2017)
We present the case of a 30-year old female with a history of abdominal pain, fever, poor oral tolerance and weight loss for 6 months. An abdominal CT scan showed marked gastric dilatation due to extrinsic compression from lymphadenopathies around the second portion of the duodenum. The upper endoscopy revealed the presence of a penetrating gastric ulcer in the greater curvature. Biopsies of the lesions showed hystiocytes with granulomatous features and Acid Fast Bacilli (AFB) positive, and the cultures grew Mycobacterium tuberculosis sensitive to Isonazid and Rifampin. Subsequently anti-TB regimen was initiated achieving great clinical and endoscopic improvement.